Time response of increases in muscle performance after Low-Level Laser Therapy (LLLT) in weight training practitioners - Costa, David Ribeiro; Costa, Davidson Ribeiro; Delpasso, Carolina Alves; Pessoa, Diego Rodrigues; Ribeiro, Luana Aparecida Pilato; Ribeiro, Camila Alves Delpasso; Nicolau, Renata Amadei (Revista Brasileira de Educação Física e Esporte, 2022)
Many studies have demonstrated the effectiveness of low-level laser therapy (LLLT) on muscle performance. Nonetheless, ideal application parameters are not known yet. The interval from the laser application moment until the time of the exercise is amongst them. In addition, the literature does not offer adequate studies that analyse different interval times in the same test in humans. Thus, the present study proposes the examination of the two distinct intervals, from the irradiation moment to the instant of the exercise performance. Forty male volunteers were recruited and randomly divided into four groups - control, placebo, immediate laser and 10 min after laser – to participate in this study. The therapy was performed with laser at 830 nm, with a power of 30 mW, energy of 3 J, during a time of 100 seconds per point irradiation, in the belly of the biceps brachii muscle. The comparison of the groups consisted in the Max force analysis, muscular power and muscle fatigue tests executed in the isokinetic dynamometer, and the recruitment of fibers by electromyography surface (EMG) and blood lactate levels in the brachial biceps muscle of weight training practitioners. A significant level of 5% (p <0.05) was considered for data analysis. The parameters adopted in the application of LLT significantly increased muscle activity (RMS) in all protocols (peak force, power and muscular endurance). In addition, LLLT was also effective in maintaining muscle performance. It was concluded that the interval time from the moment of application of the LLLT until the performance of the exercise can influence in a different way the physical capacities tested.